FUNCTIONALIZATION OF CARBON FIBRE WITH SULFUR-CONTAINING GROUPS: UDC 676.03+621.794+544.47 (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2016)
Modification of the carbon fibre Busofit with sulfur vapors in the temperature range of 400–800°C with following oxidation with hydrogen peroxide was carried out. The samples containing sulfogroups on the surface were obtained. By means of temperature-programmed desorption mass spectrometry method it is shown that the desorption of sulfogroups occurs as SO2 in the temperature range of 90–570°C. It is established that the desorption of SO2 occurs as two forms – high- and low-temperature, and the content of the high-temperature form is the highest for the sample synthesized at 600°C. By potentiometric titration method the total number of acid groups on the surface of sulfonated fibres was determined.The catalytic activity of the obtained fibres in the gas-phase dehydration reaction of isopropanol was investigated. The reaction was processed under regular heating using a fixed continuous flow reactor. The isopropanol undergoes intramolecular dehydration forming propylene. All the obtained catalysts were selective to the olefin. The temperature of complete conversion of the reactant in the reaction products is 150–220°C. The synthesized catalytic systems are more efficient catalysts for the dehydration of isopropyl alcohol compared with the previously described catalysts prepared on the basis of brominated fibres. Catalysts, obtained of brominated precursors, lose their activity when they are repeatedly used  – in the second cycle propylene yield decreased to 80% and in the third – to 63%, whereas for the most active samples obtained by treating with sulfur vapors, there is the retention of activity, propylene yield reusing these samples does not decrease.Thus, the obtained materials have a sufficiently high thermal stability and can be used as effective low-temperature acid-base catalysts if the reactions proceeds at temperatures up to 200–220°C.
Keywords: carbon fibre, surface modification, sulfogroups, dehydration of isopropyl alcohol